Les voyages reproductifs vers la Tunisie : l’intime au prisme des pratiques de l’assistance médicale à la procréation - Irene Maffi; Betty Rouland; Carole Wenger (L’Année du Maghreb)
Although in the Maghreb, and more broadly in Africa, infertility is a source of stigmatisation and social and individual suffering, many countries on the continent still lack reproductive health clinics and health professionals trained in reproductive medicine. This is due to the high cost of biomedical technologies, the lack of specialised training and the absence of national and international policies to support infertile couples in Africa. In recent years, Tunisia has emerged as a regional hub for reproductive care in the Maghreb, and more broadly in French-speaking Africa. Private IVF clinics occupy a strategic commercial position in the region, giving rise to a plurality of new reproductive mobilities. The researchers collected the stories of infertile couples crossing paths in a private fertility clinic in Tunis. In this article, we will present the stories of couples from neighbouring countries to Tunisia (Libya, Algeria), sub-Saharan Africa as well as Tunisians residing abroad (TRA) from different countries of emigration (Europe, Gulf Countries). The observations carried out within the fertility clinic, the exchanges with the medical staff as well as with the management and communication teams provide an understanding of these reproductive itineraries to Tunisia. In this article, we examine the problem of infertility in the Maghreb, the evolution of private IVF clinics in Tunisia and the dimension of intimacy through the stakes, stigmas and gendered norms that characterise medical practices in this field. In particular, our research demonstrates the persistence of certain norms that are part of an older gender regime in which women are solely responsible for infertility. We also look at the reproscapes in the Maghreb, focusing on reproductive itineraries and social conditions of the infertile couples we met, including the dematerialised spaces (internet) they resort to. In the field of health in general, as in that of infertility in particular, virtual spaces and the existence of these online communities have come to play a prominent role. They preserve intimacy and anonymity allowing Internet users affected by infertility to share their experiences and express their suffering without fear of being stigmatised. The over-representation of women on these digital platforms is indicative of gender norms that continue to dominate procreation in Maghreb countries and beyond. Articulated by the infertile North African and West African couples encountered, the transnational reproductive landscapes analysed in the paper offer an original perspective to approach the intimate in the Maghreb. In the context of ARTs, intimacy is defined on the one hand through relationships within the couple, relationships with family and loved ones; and on the other hand, in the therapeutic relationship with medical staff. The reproductive routes taken, invite us to decentralise the gaze and focus on other types of circulation from the Maghreb to the southern shore of the Sahara and even beyond (European and Gulf countries where the TRA have emigrated); to spatialise the narratives of couples in motion while grasping the globalised social transformations they characterise (biomobility, bioeconomies, biotechnologies); and to understand the sensitive nature of these narratives, which carry a very strong emotional charge. The materiality of the reproductive routes deployed (medical structures, technologies, means of transport and communication, etc.) is intertwined with other immaterial aspects intimately linked to the affective dimension behind the desire to procreate and the moral and social suffering in the face of its impossibility. The social stigma linked to the use of ARTs causes the invisibilisation of these transnational trajectories. In conclusion, our research opens up paths of analysis concerning new transnational mobilities in reproductive health as well as their moral, social, familial and emotional implications.